Second generation CD2-targeting LFA-3 fusion protein SBT115301 to restore immune homeostasis in autoimmune disease - Herve Lebrec; John Bui; Jonathan M. Clingan; Jason Do; Jason Dubovsky; Leonard Dragone; Ekaterina Gibiansky; Wing Yu Lam; Katherine Matsuda; Lauren Mihalcik; Frederick Ramsdell; Anne-Renee van der Vuurst de Vries; et al. (iScience)
Summary: In autoimmunity, an imbalance of effector (Teff) and regulatory (Treg)T cells contributes to inflammation and tissue destruction. CD2, highly expressed on Teff and at lower levels on Treg and naive T cells (Tn), is an attractive target for depleting Teff at sites of inflammation. SBT115301 is a second generation CD2-targeting fusion protein containing the cognate receptor of CD2, lymphocyte function associated antigen-3 (LFA-3; CD58). In in vitro and in vivo studies, SBT115301 preferentially decreased CD2hi-expressing Teff cells compared to Treg and Tn. In a phase 1 clinical trial, SBT115301 selectively reduced memory T cells. SBT115301 was well tolerated aside from decreases of CD4+ T cells in some participants in the highest dose IM and IV cohorts. Anti-drug antibodies decreased exposure of SBT115301 in some participants without affecting the pharmacodynamics. These data support further study of SBT115301 as a monotherapy or in combination with other drugs in autoimmune indications.